Children and Telehealth in Mental Healthcare: What We Have Learned From COVID‐19 and 40, 000+ Sessions. Issue 3 (27th January 2021) - Hoffnung, Gabriel; Feigenbaum, Esther; Schechter, Ayelet; Guttman, Daniel; Zemon, Vance; Schechter, Isaac
Abstract : Objective: Of the many impacts of COVID‐19 on contemporary healthcare is the rapid and overwhelming shift to remote telehealth (TH) service. The precise effect of TH on treatment is yet unknown, and the possible child/adult differences are an essential point of clarification for the utility of TH services and efforts to improve upon them. Methods: The current study considers data reflecting pre‐, during‐, and post‐COVID‐19 lockdown over the first six months of 2020. Data comprise records of N = 43, 294 services delivered to N = 2520 unique clients across multiple outpatient mental health sites at a Certified Community Based Mental Health Clinic (CCBHC) in Rockland County, NY, an area hard hit by COVID‐19. Results: Results demonstrate significant differences between child and adult sessions with a relative decrease in the number of child mental health services with the switch to TH in March 2020 (onset of lockdown) and a relatively rapid shift back to face‐to‐face among child services when in‐person services resumed in May and June 2020. Results further highlight significant differences between child age and service type, with psychiatry less affected by TH than psychotherapy. Conclusions: Implicit in the data is the ability to offer remotely, a high volume of ongoing behavioral intervention. Findings support TH as less preferred for children than adults while indicating that child TH is favored for psychiatry and support services, less so for psychotherapy. Implications for enhancing child TH delivery and directions for continued research include relational factors, platform (phone/video) and screen salience. HIGHLIGHTS: Rapid shift to telehealth was successful in maintaining a high volume of mental health services for both adult and children outpatient services despite pandemic. Significant differences exist between children and adults in the use of telemental healthcare as demonstrated in a robust data record of service utilization. Service type matters in telemental health with difficulty demonstrated in child psychotherapy, but not in child psychiatry and support services. Psychotherapy for children via telehealth must be enhanced to optimize impact; salience, attention and fatigue, may be important factors to be addressed for successful implementation.